(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2022)
Indonesia recognizes several legitimate religions that can be embraced by its population through Pancasila and Number 1 from UU PNPSof 1965. However, according to BPIP RI, intolerance occurs every year and there is always an increase from time to time. Even the results of a survey conducted at the University of Brawijaya on its students show that the percentage of students with high tolerance character is still very small. These two things become the basis for the author to feel it is important that research related to tolerance is carried out. Utilizing the movement of the majority of the population who adheres to Islam, the author examines tolerance in parts of the Muslim holy book, especially in Surah al-Ka>firu>n as a complete sura to be studied. This research is a literature study on the interpretation of tolerance in surah al-Ka>firu>n with the comparative method of Tafsir al-Misbah by Quraish Shihab as a representative of exegetes with an Indonesian context and Tafsir al-Maraghi by Ahmad Mustofa al-Maraghi as a comparison. and perfect interpretation. This research aims to find the similarities and differences between the two commentators and also to find a creative synthesis from the results of the analysis of the two commentators. The results of the research in this paper are that Surah al-Ka>firu>n has three important teaching points for Muslims about tolerance. First, in religion, one must hold fast to what one holds. Second, the difference between God and worship is something that cannot be mixed up and cannot be forced. Third, this surah is an affirmation that every human being will be rewarded according to his deeds. In the Indonesian context, the teachings of tolerance are not only applied when they become a majority group, but also when they become a minority group in an area. Indonesia mengakui beberapa agama sah yang dapat dianut penduduknya melalui Pancasila sebagai dasar negara dan UU PNPS No. 1 tahun 1965. Namun, menurut BPIP RI intoleransi setiap tahun terjadi dan selalu ada peningkatan dari waktu ke waktu. Bahkan, hasil survei yang dilakukan di Universitas Brawijaya terhadap mahasiswanya menunjukkan masih sangat kecil persentase mahasiswa berkarakter toleransi tinggi. Kedua hal tersebut menjadi landasan penulis merasa penting penelitian yang berhubungan dengan toleransi diangkat. Memanfaatkan pergerakan mayoritas penduduk yang menganut agama Islam, penulis meneliti toleransi pada bagian kitab suci umat islam, khususnya pada surah al-Ka>firu>n sebagai surah yang utuh untuk diteliti. Penelitian ini merupakan penelitian pustaka tentang penafsiran toleransi pada surah al-ka>firu>n dengan metode komparatif Tafsir al-Misbah karya Quraish Shihab sebagai perwakilan mufasir berkonteks keIndonesiaan dan Tafsir al-Maraghi karya Ahmad Mustofa al-Maraghi sebagai pembanding dan penyempurna penafsiran. Penelitian ini dilakukan bertujuan untuk menemukan persamaan dan perbedaan dari kedua mufasir dan juga menemukan sintesis kreatif dari hasil analisis kedua mufasir. Hasil penelitian pada tulisan ini adalah Surah al-Ka>firu>n memiliki tiga poin ajaran penting untuk umat islam tentang toleransi. Pertama, dalam beragama haruslah berpegang teguh pada yang dianut masing-masing. Kedua, perbedaan Tuhan dan ibadah merupakan hal yang tidak bisa dicampurbaurkan dan tidak bisa dipaksakan. Ketiga, surah ini merupakan penegasan bahwa setiap manusia akan diganjar sesuai dengan amal perbuatannya. Pada konteks ke-Indonesia-an, ajaran toleransi bukan hanya diterapkan pada saat menjadi kelompok yang mayoritas saja, tetapi juga pada saat menjadi kelompok minoritas pada suatu daerah.